PROTECTION OF WORKS CREATED BY ARTIFICIAL INTELLIGENCE: CHALLENGES AND PERSPECTIVES IN BRAZILIAN COPYRIGHT LAW - Ferreira, Fátima Conceição de Araújo Alves; Souza, Isadora Lis Alves Ferreira de (Editora Impacto Científico, 2025)
The rise of generative artificial intelligence (AI) challenges the traditional foundations of copyright law, particularly the concepts of authorship, originality, and ownership. In Brazil, Law No. 9.610/1998 establishes the centrality of human authorship, thereby excluding works autonomously created by AI systems. This regulatory gap creates legal uncertainty, economic risks, and ethical dilemmas, while discouraging investments and limiting the country’s participation in global innovation chains. This article examines the legal challenges of protecting AI-generated works under Brazilian copyright law, adopting a qualitative, exploratory, and comparative approach. International experiences from the United States, the United Kingdom, the European Union, and the World Intellectual Property Organization (WIPO) are analyzed, revealing diverse solutions — ranging from the exclusion of copyright protection to derivative attribution and the establishment of sui generis regimes. Through bibliographic review and documentary analysis, three main approaches are identified: (i) treating AI-generated works as public domain; (ii) granting derivative rights to programmers or users; and (iii) creating a sui generis regime. The study concludes that a hybrid model is the most promising alternative for Brazil, combining derivative protection in cases of significant human intervention with a specific regime for autonomous AI productions. The findings contribute to the academic debate and provide normative insights for legislative reform, interpretative guidelines, and Brazil’s active participation in WIPO forums. The article argues that building a regulatory framework adapted to the AI era is crucial to ensure legal certainty, preserve the centrality of human creativity, and foster technological innovation. DOI: https://doi.org/10.56238/edimpacto2025.084-013